Voltammetric studies on vitamin E in organic solvents and within lipid bilayer membranes - Yao, Wei Wei (2011)
A series of model tocopherol compounds with differing degrees of methyl substitution around the aromatic ring were studied by variable scan rate (0.1- 500 V s-1) cyclic voltammetry experiments in CH3CN and CH2Cl2. On short voltammetric timescales α-TOH is oxidised in a chemically reversible –2e–/–H+ process to form a phenoxonium cation (α-TO+). The equilibrium and rate constants associated with the chemical steps were estimated by digital simulations of the variable scan rate data over a range of temperatures (T = 253-313K). α-Tocopherol films were deposited on the surface of gold, glassy carbon and platinum electrodes and their voltammetric behavior examined in aqueous solutions between pH 3 and 13. The voltammetric mechanism involved α-tocopherol being oxidised in a –2e–/–H+ process to form a phenoxonium cation (similar to the experiments in non-aqueous solvents), which underwent rapid reaction with water (or –OH¯ at pH > 7) and rearrangement to form α-tocopherol quinone in a chemically irreversible process. Electrochemical experiments were also performed by incorporating α-tocopherol into lecithin multilayers deposited onto the electrode surfaces. The results were very similar to those obtained for pure α-tocopherol films. α-tocopherol was oxidised to α-tocopherol quinone within the lecithin multilayers. However, the reduction process of α-tocopherol quinone appeared to be less chemically reversible as the pH was increased above pH 7. Two methods were used to incorporate α-tocopherol within the lecithin multilayers and both methods yielded similar electrochemical results.